FEASIBILITY OF REDOX REACTIONS THROUGH FORMAL REDOX POTENTIAL VALUES: Short Communication - Farrukh, M Akhyar; Naqvi, Iftikhar Imam (Biological Sciences - PJSIR, 2004)
In a complexation reaction, where one or more of the compo- nents of the redox couple are involved, it is very difficult to have the exact knowledge of the activities to determine the standard redox potential values. Therefore, at specified con- centration Nerst equation may be modified to calculate the formal potential by replacing the activities to concentrations (Braun 1985). The various parameters exploited for facilita- ting such reactions have been complexation of the reacting species, nature of acid or base and pH, formation of hydroxo complexes with metal ions, formation of hydronium salt of anionic metal complexes (Bailer et al 1973; Farrukh and Naqvi 2002; Kimura 1999). In addition to that, the factors described below also alter the respective standard redox potential val- ues. (1) Eo decreases with increasing the oxidation number of an element due to an increase in ionization potential. (2) Eo also decreases within a period as ionization potential increases with increasing atomic number. (3) Ionization potential values of the transition metal series increase with increasing atomic number, accordingly Eo values get decreased within a period.